KAMPUNG MUSLIM SAREN JAWA DI BALI TIMUR: DINAMIKA KOMUNIKASI SOSIAL DALAM MEMBENTUK HARMONI SOSIAL - Yoga, I Dewa Gede; Sutama, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2025)
Kampung Saren Jawa is a unique example of how different cultural and religious identities can coexist in a multicultural society. This study aims to understand how social interaction, communication between individuals, and the influence of cultural and religious values ​​​​in creating social harmony amidst the diversity of Bali which is better known for its Hindu majority. Qualitative research methods were used with a qualitative descriptive approach involving in-depth interviews with village residents, religious leaders, and local government representatives. The results of the study show that social communication in Kampung Saren Jawa is strongly influenced by the values ​​​​of friendship, tolerance, and mutual respect between individuals. Despite religious and cultural differences, openness in communication and strengthening social ties based on mutual cooperation and local traditions play an important role in maintaining harmony. The role of community leaders, both from religious and customary circles, is also crucial in mediating differences and building mutual respect. These findings provide important insights for the study of social communication and interfaith interaction in a multicultural context, as well as its relevance in strengthening social cohesion in Indonesia, especially in areas with high ethnic and religious diversity.